OPENING ADDRESS TO ARTICLE T.V. KAIGORODOVA, E.V. KIRSANOVA «THE POSITION OF THE WORLD HEALTH ORGANIZATION ON THE DEVELOPMENT OF NURSING AND MIDWIFERY» - A.A. Modestov (Union of pediatricians of Russia, 2011)
.